Pengembangan Bahan Ajar Interaktif Berbasis Genially Untuk Meningkatkan Pemahaman Materi Teks Anekdot pada Siswa Kelas X SMK di Sekolah Jambi - Haryanti, Inggit; Al Muthia, Muzkia; Syifa, Nadia Ayu; Sinaga, Nisa Sweet; Tarigan, Widia Lauranita Br; Azizah, Nurul; Hutagalung, Trisnawati (CV. Rayyan Dwi Bharata, 2025)
This study aims to develop Genially-based interactive teaching materials in accordance with the Merdeka curriculum to improve students' understanding of anecdotal texts in Grade X of vocational schools in Jambi. This study uses the Research and Development (RD) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data was obtained through interviews with teachers and students, which revealed that the lecture method was ineffective and that the hikayat text material was the most difficult to understand. As many as 70% of students liked Indonesian language lessons and actively told stories in anecdotal text learning, with a preference for learning outside the classroom. The study used a descriptive qualitative approach to explore experiences and perceptions related to learning and the development of interactive teaching materials on the Genially platform.